Human papillomavirus infection of the oesphagus and its association with squamous cell carcinoma : a restropective study of cases seen at Chris Hani Baragwanath hospital in 2009 and 2010 - Van der Byl, Dawn-Lee (My University, 2014)
There are two principal types of oesophageal carcinoma with squamous cell carcinoma being the most common globally. There are several different etiological factors in the development of oesophageal squamous cell cancer (OSCC). The significance of these risk factors appears to vary by region. The human papillomavirus has been implicated in the aetiology of OSCC. Furthermore, it has been postulated that the differences in the prevalence of HPV in OSCC is related to the geographical region in which the study was conducted with HPV playing a more significant role in high risk areas. Aim The aim of this study was to establish the presence or absence of HPV infection in the oesophagus and any association it may have with oesophageal squamous cell carcinoma. Materials and methods All cases of oesophageal squamous cell carcinoma that were diagnosed between 01 January 2009 and 31 December 2010 at Chris Hani Baragwanath Hospital were included in the study. All the cases were assessed for the presence or absence of condylomatous atypia. PCR was performed on all the cases as well as on 10 v cases of normal control oesophageal biopsies. PCR was performed using the GP5+ and GP6+ primers. Results The database search revealed 96 eligible cases of which 95 showed amplification of the β-globin gene and underwent PCR. Of these, two cases showed histological features of condylomatous atypia. All 95 cases failed to demonstrate the presence of HPV DNA by PCR. Conclusion HPV is a common infection in the South African population and is known to be carcinogenic in other sites. Its role in OSCC has remained controversial, however, this study does not support the theory that HPV has a role to play in the pathogenesis of OSCC.
There are two principal types of oesophageal carcinoma with squamous cell carcinoma being the most common globally. There are several different etiological factors in the development of oesophageal squamous cell cancer (OSCC). The significance of these risk factors appears to vary by region. The human papillomavirus has been implicated in the aetiology of OSCC. Furthermore, it has been postulated that the differences in the prevalence of HPV in OSCC is related to the geographical region in which the study was conducted with HPV playing a more significant role in high risk areas. Aim The aim of this study was to establish the presence or absence of HPV infection in the oesophagus and any association it may have with oesophageal squamous cell carcinoma. Materials and methods All cases of oesophageal squamous cell carcinoma that were diagnosed between 01 January 2009 and 31 December 2010 at Chris Hani Baragwanath Hospital were included in the study. All the cases were assessed for the presence or absence of condylomatous atypia. PCR was performed on all the cases as well as on 10 v cases of normal control oesophageal biopsies. PCR was performed using the GP5+ and GP6+ primers. Results The database search revealed 96 eligible cases of which 95 showed amplification of the β-globin gene and underwent PCR. Of these, two cases showed histological features of condylomatous atypia. All 95 cases failed to demonstrate the presence of HPV DNA by PCR. Conclusion HPV is a common infection in the South African population and is known to be carcinogenic in other sites. Its role in OSCC has remained controversial, however, this study does not support the theory that HPV has a role to play in the pathogenesis of OSCC.